Growth factors and pro-inflammatory cytokines in regenerative procedures - (:unkn) unknown (MEDIMOND S R L, 1997)
Bone is able to repair and regenerate. In periodontics, periodontal regeneration is described as reconstitution of lost supporting tissues including alveolar bone, cementum, periodontal ligament, and gingival attachment. This process is regulated by the local production of growth factors. Based on current knowledge, possible growth factors that may be involved in bone regeneration are platelet-derived growth factor (PDGF), insulin-like growth factor (IGF), epidermal growth factor (EGF), basic fibroblastic growth factor (bFGF), transforming growth factor-beta (TGF-beta), and bone morphogenic proteins (BMPs). Local regulation of osseous wound healing reflects the cumulative response to the growth factors and cytokines present in the environment. In inflammatory disease, the presence of proinflammatory cytokines, IL-1 and TNF-alpha is well established. These cytokines are potent bone resorptive cytokines and are generated in osseous inflammation. Therefore, the inhibitory effects of these cytokines might involve the downregulation of potent bone growth factors including PDGF. In our studies, we demonstrated that TNF-alpha significantly reduces PDGF-AA binding by decreasing the number of PDGF-alpha receptor subunits on the surface of normal human osteoblastic cells resulting in decreased in PDGF-AA stimulated tyrosine kinase activity. When saturating concentrations of TNF-alpha were used, the addition of IL-1 further inhibited PDGF-AA binding and further decreased surface expression of PDGF-alpha receptors. What we believe is that well-balanced resorption and formation events in bone are interrupted in favor of bone resorption in inflammatory disease such as rhematoid arthritis and periodontitis due to the presence of proinflammatory cytokines, IL-1 and TNF-alpha. This interruption may be mediated in part through a decrease in the PDGF-alpha receptor on osteoblastic cell surfaces by these proinflammatory mediators. For future experiments, it would be beneficial to show the effect of these cytokines, IL-1 beta and TNF-alpha on the stimulation of bone cells by other growth factors important in bone regeneration. Furthermore, the blocking of negative effects of these bone resorptive cytokines by using the recombinant natural inhibitors of these cytokines, such as IL-1 beta receptor antagonist and TNF-alpha soluble receptor protein might be another approach to burst the response of bone cells to growth factors in the presence of inflammation.